1984
DOI: 10.1128/aac.25.6.742
|View full text |Cite
|
Sign up to set email alerts
|

Strains of varicella-zoster virus resistant to 1-beta-D-arabinofuranosyl-E-5-(2-bromovinyl)uracil

Abstract: Strains of varicella-zoster virus resistant to 1-p-D-arabinofuranosyl-E-5-(2-bromovinyl)uracil (BV-araU) were isolated from varicella-zoster virus-infected Vero cells which were pulse-treated with 5-iododeoxyuridine or 5-bromodeoxyuridine or both and then treated with BV-araU. These BV-araU-resistant strains (BVaraUr) could not be isolated from varicella-zoster virus-infected cells treated with BV-araU alone and had reduced viral thymidine kinase activity. Two offive BV-araUr strains were also resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Several of these triphosphates act selectively on the DNA polymerase level. Many HSV-1 and VZV strains that are resistant to various nucleoside analogs have been described (4,5,7,9,21,24,(26)(27)(28). We and others have previously shown that VZV strains with deficient TK activities have a decreased susceptibility to acyclic guanosine analogs like ACV and 2HM- Cytomegalovirus, which lacks a virus-induced TK, is not susceptible to these compounds but is susceptible to other modified nucleosides that can be phosphorylated by cellular enzymes (15).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these triphosphates act selectively on the DNA polymerase level. Many HSV-1 and VZV strains that are resistant to various nucleoside analogs have been described (4,5,7,9,21,24,(26)(27)(28). We and others have previously shown that VZV strains with deficient TK activities have a decreased susceptibility to acyclic guanosine analogs like ACV and 2HM- Cytomegalovirus, which lacks a virus-induced TK, is not susceptible to these compounds but is susceptible to other modified nucleosides that can be phosphorylated by cellular enzymes (15).…”
Section: Discussionmentioning
confidence: 99%
“…In the many reports about resistant mutants to antiherpesvirus drugs, almost all had mutations for the induction of or for the affinity to TK or DNA polymerase (5,6,10,17,25). In this study, we have revealed that in addition to the difference in viral TK activities, the size of the thymidine and thymidine phosphate pools and TS activity in HSVinfected cells are also important to the susceptibility of HSV to antiherpesvirus drugs.…”
Section: Methodsmentioning
confidence: 67%
“…In this study, however, drug-resistant mutations of VZV were not detected at this time during the interval studied. In addition, the drug susceptibility was observed to be generally comparable for isolates obtained before and during brovavir therapy, and VZV has been shown to be relatively unlikely to become drug-resistant through mutation (10). Viral mutation is unlikely to occur at least during such a short period of brovavir treatment for zoster conducted in the present clinical study, although idoxuridine and acyclovir have been found to induce drug-resistant mutants in the treatment of herpes simplex (2, 9).…”
Section: Brovavir [1-b-d-arabinofuranosyl-e-5-(2-bromovinyl) Uracil; mentioning
confidence: 76%